A Study of Anticancer Activity for Partial Purified Urease Isolated from Lagonychium farctum Plant - Allawi, Mohammed Hasan; Abed, Mohamed Qais (Al-Nahrain Journal of Science, 2018)
This study included two experiments, the first of which included the investigation of the urease enzyme in the plant extract of the Lagonychium farctum, which included the extracts of the seeds, leaves and stems the plant. The results, showed that the highest enzymatic and quality efficacy of urease was in seed extract of the Lagoonchium farctum. The optimal conditions for enzyme extraction were determined using different solution, pH and temperature. The Potassium Phosphate Solution at 0.02 μl pH 8 was the homogenous enzyme extract, with an enzymatic concentration of 3.195 U/ml. The optimum reaction time for enzyme extraction was 30 min, giving an enzyme activity of 3.274 U / ml. The optimum reaction time for enzyme extraction was 30 minutes where it gave enzymatic efficacy of 3.274 U/ml. The purification was by several steps including ammonium sulphate deposition with different precipitation ratios. The optimum saturation was 50 %, followed by ionic exchange on the DEAE-cellulose column and gel filtration on the Sephadex G-200 column. The purification time was 29.6 and the enzyme yield was 75 %. The second experiment included study of the effectiveness of the enzyme Urease as an Anticancer activity. Results showed that the urease enzyme had an inhibitory effect on the breast cancer line MCF7; it has been shown to be effective in the direction of breast cancer when the concentration of the partially purified enzyme is increased while in contrast to the natural cell line WRL68.